Airway Microbiota Determines Innate Cell Inflammatory or Tissue Remodeling Profiles in Lung Transplantation - Bernasconi, Eric; Pattaroni, Céline; Koutsokera, Angela; Pison, Christophe; Kessler, Romain; Benden, Christian; Soccal, Paola M.; Magnan, Antoine; Aubert, John-David; Marsland, Benjamin J.; Nicod, Laurent P. (American journal of respiratory and critical care medicine, 2016)
In lung transplant recipients, long-term graft survival relies on the control of inflammation and tissue remodeling to maintain graft functionality and avoid chronic lung allograft dysfunction. Although advances in clinical practice have improved transplant success, the mechanisms by which the balance between inflammation and remodeling is maintained are largely unknown. To assess whether host-microbe interactions in the transplanted lung determine the immunologic tone of the airways, and consequently could impact graft survival. Microbiota DNA and host total RNA were isolated from 203 bronchoalveolar lavages obtained from 112 patients post-lung transplantation. Microbiota composition was determined using 16S ribosomal RNA analysis, and expression of a set of genes involved in prototypic macrophage functions was quantified using real-time quantitative polymerase chain reaction. We show that the characteristics of the pulmonary microbiota aligned with distinct innate cell gene expression profiles. Although a nonpolarized activation was associated with bacterial communities consisting of a balance between proinflammatory (e.g., Staphylococcus and Pseudomonas) and low stimulatory (e.g., Prevotella and Streptococcus) bacteria, "inflammatory" and "remodeling" profiles were linked to bacterial dysbiosis. Mechanistic assays provided direct evidence that bacterial dysbiosis could lead to inflammatory or remodeling profiles in macrophages, whereas a balanced microbial community maintained homeostasis. The crosstalk between bacterial communities and innate immune cells potentially determines the function of the transplanted lung offering novel pathways for intervention strategies.